Contributions of Islamic Civilization to The Mathematics Development - Liya Khaulah Asy-Syaimaa' Hussain; Ahmad Faizuddin Ramli (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
The development of Islamic civilization goes hand in hand with physical and spiritual development. This development can be highlighted since the beginning of the golden age of Islam that witnessed the development of knowledge by Muslims scholars in various disciplines, including mathematics. The discourse in mathematical science only involves numbers, letters, and formulas. Muslims scholars took them as instruments to manifest the greatest of God. This paper investigates the contributions of Muslim scholars in Mathematics. The method of this study is qualitative through literature review. The resulting study found that the Quran became a source of inspiration to Muslim scholars in mathematics that form the branch of knowledge such as number theory, arithmetic, algebra, and geometry. This paper also promotes Islamization of Knowledge and its necessity to solve current Muslim world’s educational problems.